Bumpy Rides: School‐to‐work Transitions in South Africa. (19th September 2017) - Pugatch, Todd
Abstract: Re‐enrollment in school following a period of dropout is a common feature of school‐to‐work transitions, but has been largely ignored in the literature on sequential schooling choice. I quantify the importance of the option to re‐enroll in school‐to‐work transitions in South Africa. I estimate a model of sequential schooling choice using a panel that contains the entire schooling and labor market histories of sampled youth. The model incorporates Bayesian learning about academic ability and the probability of employment in response to outcomes from past choices, with updated beliefs influencing the expected returns to human capital investment and labor market participation. I conduct a policy simulation under which re‐enrollment prior to high school completion is completely restricted, raising the opportunity cost of dropout. The resulting fall in dropout increases school attainment, raising the proportion of students completing at least 12 years of schooling by 5 percentage points. The corresponding income gains fail to compensate for the welfare loss incurred from removing the option to re‐enroll, however. The results suggest that the option to re‐enroll is an important component of the incentives South African youth face when making schooling decisions.